Uptake of nutrients in vegetables grown on FGD-gypsum-amended soils - Yutdanaiyodthongdee (2018)
This research evaluated the effects of using flue gas desulphurization gypsum (FGDG) for growing of some agronomic crops. The FGDG was added to soil at 0, 2.5, 5.0 and 7.5% by weight. The test plants, Chinese kale and green bean, were grown and harvested after 45 days and 60 days, respectively. Application ot FGDG at all ratios significantly increased pH of the soil, due to the lime containing in FGDG. The heavy metals content in plants grown in the FGDG treated tanks were not significantly ditterent trom those ot the control tank. From the ten studied elements in Chinese kale and green bean seed tissues (As, Ca, Cd, Cr, Cu, K, Mg, Na, Pb, and Zn), the content of five toxic elements (As, Cd, Cr, Cu, and Pb) were very low and not significantly influenced by FGDG, while the content of some nutrient elements (K, Ca, Mg) in the plant tissues growing in Ft3DG treated soil were higher than the control. Concentration of some micronutrients (Cu and Zn) in plants decreased with increasing dose of FGDG. There has not been any negative effect from applying up to 5.0% FGDG in soil. The results showed possibility of using FGDG as soil amendment in terms of agricultural production and safety.